Comprehensive Review of Nursing Education and Clinical Practice - Alharoubi, Salha Ali Salman; Alasmary, Amal Mufareh Abdullah; Alkhaledi, Wedad Jubran Mohammed; Asiri, Safiah Ayed Ali; Al zamil, Rawaby Shara jurbua; Saleh, Zahra Rdan; Alwan, Gharam Ali (Journal of Ecohumanism, 2024)
Nursing education has a significant function in the development of the workforce in providing healthcare, and it acts as a virtual determinant of the quality of patient care. The changing face of healthcare, students with different demographics, advanced technologies, and specializing rather than generalizing healthcare needs require change in preparing the nurses for practice. This paper aims to review the existing state of nursing education, its problems, students’ and professionals’ challenges, and the incorporation of best evidence and information technology into the nursing curricula. The review also points to the need to encourage nurse education and professional development to keep nurses competent throughout their working years. By synthesizing the literature reviewed in this paper, it has been possible to offer input on the future of nursing education, clinical practice, and the workforce.